The right-side perceptual bias in aging determined in a laboratory setting and during a virtual driving task - Heikki Hämäläinen; Faramosh Rashid Izullah; Mika Koivisto; Fiia Takio; Mika Luimula (WILEY, 2022)
Spatial perceptual rightward bias which was originally described in Dichotic Listening studies seems to be a general phenomenon. This bias is age dependent, being evident in children with developing executive functions, and emerging again at older age as a function of aging and the declining executive functions. In the two studies presented here we compared the performance of young and elderly adults in spatial divided attention tasks with auditory and visual stimuli when the stimulus detection performance was measured in separate sessions in a laboratory setting (Study I), to performance when the same types of stimuli were mixed with a task in which the subject's primary objective was to drive a car in a virtual environment (virtual reality; Study II). The aim was to see if the perceptual bias could be detected and also to look at how it would differ in these two situations. 90 right-handed subjects (50 young and 40 elderly) participated in Study I and 84 subjects (64 young and 20 elderly) participated in Study II. Study I showed the rightward bias to be more evident in the elderly subjects in both modalities and in more demanding tasks. Study II revealed that in the triple task the spatial perceptual bias was evident in both modalities for the elderly participants when the conditions were more demanding. An interesting finding concerning the right-side perceptual bias was the simultaneous occurrence of left-side driving errors, i.e. crossing the lane border to the left especially by the elderly. Both of these biases may reflect the asymmetries of the attention-related neuronal networks.